Non-Contact Detection of Breathing Using a Microwave Sensor - Massimo Marsili; Walter Castellani; Gianna Camiciottoli; Sergio Boncinelli; Carlo Atzeni; Massimiliano Pieraccini; Guido Luzi; Gilberto Grazzini; Devis Dei; Juri Lo Dico (Sensors, 2009)
In this paper the use of a continuous-wave microwave sensor as a non-contact tool for quantitative measurement of respiratory tidal volume has been evaluated by experimentation in seventeen healthy volunteers. The sensor working principle is reported and several causes that can affect its response are analyzed. A suitable data processing has been devised able to reject the majority of breath measurements taken under non suitable conditions. Furthermore, a relationship between microwave sensor measurements and volume inspired and expired at quiet breathing (tidal volume) has been found.